ANALYSIS OF THE OWNERSHIP STATUS OF REMPANG CUSTOMARY LAND AND ITS IMPLICATIONS FOR HUMAN RIGHTS VIOLATIONS - Nurhalizah, Rani; Muslim, Muslim (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2024)
Agrarian conflicts frequently lead to land disputes due to ambiguities in existing regulations, such as overlapping claims, which result in uncertain land status. This research focuses on the conflict involving Rempang land, where a dispute emerged between PT Elok Makmur Graha, an investment entity, and the indigenous Rempang community. This conflict culminated in forced evictions of the Rempang community, constituting a violation of human rights. The objective of this research is to examine land rights and assess the extent of legal protection provided by the government to uphold the human rights of the Rempang community. Utilizing normative legal research methods and a conceptual approach, the research finds that customary land, traditionally held by the community, is not adequately recognized under Law No. 24 of 1997 concerning Land Registration, specifically Article 9, paragraph (1), which excludes customary land from land certificate registration.Keywords: Ulayat Land, Human Rights Protection, Agrarian Conflict.